Engineering a Clinical Force Measuring Walker for Patients Recovering from Median Sternotomy - LaPier, Ansel K. (International Journal of Innovative Research in Medical Science, 2022)
Background: Patients often need the use of their arms to assist with functional activities, but after median sternotomy, pushing is frequently limited to less than 4.5 kg. No method exists to objectively measure arm weight bearing in clinical settings. This project aimed to design, construct, and test a walker for patients recovering from median sternotomy to prevent excessive bone stress during ossification. Methods: First, a qualitative study was conducted to obtain critiques of a Clinical Force Measuring (CFM) Walker prototype from rehabilitation professionals. Key statements and phrases were coded that allowed “themes” to emerge from transcribed interviews, which guided device revisions. Next, a second CFM Walker prototype was designed based on the qualitative data and device criteria/constraints and finally tested. Results: The result was fabrication of a new lightweight, streamlined, and cost-effective prototype walker with a simple visual display and auditory cue with upper limit alarms. Key features included attachments for medical equipment and thin film force-sensing resistors integrated into the walker handles that progressively activated 3 LEDs and a buzzer when arm force exceeded programmed thresholds. Conclusions: The innovative CFM Walker will help patients with restricted upper extremity weight bearing, especially elderly adults, recover safer and faster in the future.